Answer:
5. 8/6x + 2
6. -4x - 2
7. y=3
Step-by-step explanation:
Answer:
![-4^{4}](https://tex.z-dn.net/?f=-4%5E%7B4%7D)
Step-by-step explanation:
Reduce the expression -4^2×4^2
Calcualte the product and you get -4^4
If you want the alternative form is will be -256
Hope this helpsʕ•ᴥ•ʔ
Answer:
Therefore x=9
Step-by-step explanation:
Give that,
log x+ log (x-3) = log 54
log x(x-3) =log 54 [
]
x(x-3) = 54
Now expand the above equation to get a quadratic equation
x²-3x=54
⇒x²-9x+6x-54=0
⇒x(x-9)+6(x-9)=0
⇒(x-9)(x+6)=0
⇒x-9=0 or, x+6=0
⇒x=9,-6
Now putting x= -6 in the given expression,
log(-6)+log(-6-9)=log 54.
Since log (-6) does not exist.
Therefore x=9